Steganography using Energy-LSB Embedded Method (Al-Mansour Journal, 2022)
In this paper embedding approach based on energy function and a Least Significant Bits (LSB) method was proposed to hide a secret message in a highly color or intensity part of an image that divided into blocks. Even with a different format types and different sizes of the selected images to cover and hide a variable size of a message, the quality results, show that the less distortion of the stego image as compared with the cover image and the proposed algorithm is robust to hide a randomize secret message even with decreasing the sizes of the blocks.
Keywords: Steganography; Energy; (Least Significant Bits) LSB; MSE; PSNR